2015
DOI: 10.1017/thg.2015.94
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Risk of Monochorionic Twins in IVF Pregnancies From the Perspective of a Prenatal Diagnosis Unit

Abstract: The aim of the present work was to estimate the risk of monochorionic twin (MCT) pregnancies in in vitro fertilization (IVF) cycles using data from a prenatal diagnosis unit. This was a retrospective cross-sectional study reporting on the frequency of IVF pregnancies among women attending a prenatal diagnosis service specifically dedicated to the management of monochorionic pregnancies. The observed rate was compared with the local regional rate of IVF births (2.2%). A binomial distribution model was used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(73 reference statements)
2
3
0
1
Order By: Relevance
“…TTTS is the most common cause of excess mortality in monochorionic twin gestations 36 , however we did not observe a higher incidence of TTTS in the IVF/ICSI group. This in agreement with the results of earlier studies 13,14,16,28 . One study even reported a lower incidence of TTTS in MCDA pregnancies conceived after IVF 37 , but the authors excluded pregnancies that resulted in the loss of one or both twins, which is often the result of TTTS.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…TTTS is the most common cause of excess mortality in monochorionic twin gestations 36 , however we did not observe a higher incidence of TTTS in the IVF/ICSI group. This in agreement with the results of earlier studies 13,14,16,28 . One study even reported a lower incidence of TTTS in MCDA pregnancies conceived after IVF 37 , but the authors excluded pregnancies that resulted in the loss of one or both twins, which is often the result of TTTS.…”
Section: Discussionsupporting
confidence: 93%
“…The rate of IVF/ICSI in our cohort was 12%, which may seem high compared with some series 14,16 , but it is comparable with, or even lower than, the rate in other studies 13,28 . This high proportion of IVF/ICSI pregnancies may be related to the reimbursement policy for IVF treatment in Belgium.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations